Precipitation Redistribution Method for Regional Simulations of Radioactive Material Transport During the Fukushima Daiichi Nuclear Power Plant Accident. Issue 18 (22nd September 2018) - Saya, Akane; Yoshikane, Takao; Chang, Eun‐Chul; Yoshimura, Kei; Oki, Taikan
Abstract: To reproduce more accurate deposition maps of radioactive materials released in the Fukushima Daiichi Nuclear Power Plant accident in March 2011, our study focuses on the uncertainty of atmospheric transport simulations caused by precipitation. In our new method, simulated wet deposition distribution of 137 Cs is modified by high‐resolution radar rain gauge data of observed precipitation. Sensitivity experiments are conducted to examine the impact of using both different reanalyzed meteorological data sets as boundary condition and the observation data of precipitation as the redistribution of simulated precipitation. Among the results, the experiment modified by high‐resolution radar rain gauge data realized the most accurate cumulative 137 Cs deposition from 18 to 27 March. While the meteorological field is reasonably simulated in the atmospheric transport model in the experiments, the results showed that applying observed precipitation also contributes to improve the accuracy of simulated wet deposition amount. Key Points: Wet deposition of 137 Cs simulated by the regional isotope tracer model is redistributed in correspondence with observed precipitation To reproduce wet deposition, both high‐resolution boundary condition in the model and highly accurate simulated precipitation are necessary In our results, validation is evaluated differently depending on the time boundary of the measurement of 137 Cs fallouts